Dvoinikut - Volev, Nikolai (Bulgaria : Savremennik at Boyana Film Studio, 1979)
Assistant professor Denev is a talented scientist who cannot properly manage his time, caught between his scholarly and public activities. Suddenly he comes up with the idea of bringing his look-alike cousin Ivan from the countryside. Ivan appears on the committee boards and wherever his cousin’s presence is required, while Denev attends to his research work. With uncertainty at first but gradually gaining confidence Ivan takes up his new role and his determination to gain material benefits at every occasion becomes threatening. When at last the double seduces his cousin's colleague, who had been attracted to the scientist, the latter finally tries to put the record straight and chase the double from his life.
Keywords: Fiction films